Primary school reopenings and parental work. (10th March 2022) - Beauregard, Pierre‐Loup; Connolly, Marie; Haeck, Catherine; Molnár, Tímea Laura
Abstract: In this paper, we exploit the geographical pattern of primary school reopenings during the COVID‐19 pandemic in Canada to estimate the impact of school reopenings on parental employment and work hours. We use a triple‐difference approach, in which we first compare parents of primary‐school children in regions where schools reopened to similar parents in regions where schools remained closed and add parents of older, secondary‐school children as an additional control group. We estimate the impact of school reopenings separately for mothers and fathers, and for single parents and parents living in dual‐parent households. We find a positive impact of school reopenings on employment and on actual hours worked. The effects tend to be stronger for single mothers, but are also present for mothers and fathers in dual‐parent households in the spring of 2020. Overall, single mothers experienced an 18 percentage point increase in their employment at work rate following school reopenings. We also split our sample according to whether the job can be done from home, and find stronger impacts for those whose jobs cannot easily be done from home. Résumé: La réouverture des écoles primaires et le travail des parents . Dans cet article, nous exploitons la dispersion géographique des réouvertures d'écoles primaires durant la pandémie de COVID‐19 au Canada afin d'estimer l'impact des réouvertures d'écoles sur l'emploi des parents et leurs heures de travail. Nous utilisons une approche de triple différence, dans laquelle nous comparons tout d'abord les parents d'enfants à l'école primaire dans les régions où les écoles ont réouvert aux parents similaires dans les régions où les écoles sont restées fermées, puis nous ajoutons les parents d'enfants plus âgés, à l'école secondaire, comme groupe de contrôle additionnel. Nous estimons l'impact des réouvertures d'écoles séparément pour les mères et les pères, et pour les parents monoparentaux et ceux dans les ménages à deux parents. Nous trouvons un impact positif des réouvertures d'écoles sur l'emploi et les heures effectivement travaillées. Les effets tendent à être plus marqués pour les mères monoparentales, mais sont aussi présents pour les mères et les pères dans les ménages à deux parents au printemps 2020. En tout, les mères monoparentales ont connu une hausse de 18 points de pourcentage de leur taux d'emploi (au travail) suite aux réouvertures d'écoles. Nous séparons aussi notre échantillon selon que l'emploi puisse être fait de la maison et trouvons des impacts plus forts pour ceux dont l'emploi ne peut facilement être fait de la maison.